ASSESSMENT OF SAFETY PARAMETERS FOLLOWING REPEATED ARTEMISIN-BASED TREATMENTS OF MALARIA-INFECTED PATIENT LIVING IN ENDEMIC AREA OF BURKINA FASO. (12th February 2017) - Coulibaly, Sam; Soulama, Issiaka; Kabore, Jean Moïse; Ouattara, San Maurice; Bougouma, Edith; Ouedraogo, Alphonse; Sanon, Souleymane; Amidou, Diarra; Sombie, Benjamin; Ouedraogo, Amidou; Kargougou, Désiré; Ouattara, Daouda; et al.
Abstract : Background: Artemisinin-based combination therapies (ACTs) constitute the worldwide recommended antimalarial drug as first-line treatment of uncomplicated malaria. However, the safety of repeated administration of a given ACT is poorly documented. The aim of this study was to evaluate the safety of repeated administration of ACTs in malaria patients over a period of 2 years. Methods: A randomised, open-label phase IIIb/IV comparative three arms trial comparing pyronaridine tetraphosphate/artesunate (PA), dihydroartemisinine-pipéraquine (DHA-PQP) and artesunate-amodiaquine (ASAQ) was carried out in Burkina Faso site as part of the WANECAM (West African Network for Clinical Trials of Antimalarial Drugs) global study. The study involved patients from 6 months of age presenting with uncomplicated malaria (fever/history of fever and Plasmodium spp. density <200, 000). The patients were treated repeatedly with the same ACT they were assigned to at enrolment. Safety assessments consisted with electrocardiographic and laboratory evaluations. Results: A total of 763 participants with uncomplicated microscopically confirmed Plasmodium spp. malaria were included. The proportion in ASAQ treated patients with creatinin abnormal value did not differ significantly between episode 1 and repeated malaria episodes (16.14% versus 13.98%, p=0.31). The proportion of patients with abnormal value of ALAT decreased significantly from baseline (25/234 versus 16/787, p< 0.01), but there is no difference in haemoglobin mean between the different episode (p>0.05) within each treatment arms. No evidence was found in the risk of QTc interval prolongation during repeated treatment in any arm. Conclusions: The findings showed that safety was similar on first malaria treatment versus retreatment of subsequent episodes. The safety parameters were also comparable between the 3 treatment arms. These results support the repeated use of the three ACTs in uncomplicated malaria patients in Burkina Faso.